The Legality of Land Ownership Right that Changes in Position and Size (Case Study of Natural Liquefaction Disaster in Palu City) - Maisa, Maisa; Muliadi, Muliadi; Windiahsari, Windiahsari (Universitas Negeri Semarang, 2024)
This study endeavors to accomplish two primary objectives: firstly, to evaluate the legal status of land ownership rights impacted by the liquefaction natural disaster in Palu, particularly focusing on instances where there are alterations in position and dimensions. Secondly, it aims to scrutinize the actions undertaken by land rights holders to secure legal ownership of land affected by such changes, particularly through engagements with the Palu City National Land Agency. Employing a juridical-empirical approach, the research illuminates two pivotal findings: firstly, that natural disasters, including liquefaction, can induce substantial shifts in land position, potentially complicating the legality of ownership and precipitating disputes among neighboring landowners. Secondly, it reveals that land rights holders commonly interface with the National Land Agency to rectify alterations in land position and size, underscoring the imperative of prompt reporting to ensure accurate measurement and documentation. The study posits two recommendations: firstly, advocating for timely reporting to the National Land Agency by affected communities to facilitate precise measurement and documentation of land shifts. Secondly, advocating for governmental enactment of specialized regulations addressing land transfers, thereby augmenting legal certainty for affected communities.